Assessment of the food safety policies of three selected catering companies - Loverio, Jennifer P. (College of Home Economics, 2011)
This study made an attempt to assess the food safety policies of three catering companies in Pasay and Malolos City. Applying the survey research method and using purposive sampling participants in the study were interviewed. Focus group discussion (FGD) was conducted to assess the knowledge, attitude and practices of the managers, supervisors and employees from the three selected catering companies. Data analysis utilized mean and frequency measures. The study likewise used a monitoring checklist to audit the catering companies compliance to food safety policies. Findings revealed that all respondents were knowledgeable on the food safety policies of their companies. However, their knowledge and positive attitude towards food safety policies were not reflected in the workplace. Results indicate that the most commonly violated food safety practices among the catering companies were personal hygiene and presence of unauthorized personnel in the kitchen because the employees lack food safety orientation and training. On the other hand, the three catering companies complied with the policy of obtaining a sanitary permit to operate their business. However, data showed that there were employees who did not have health permits violating the provision stipulated in the Sanitation Code of the Philippines (P.D. 876). On the contrary, the respondent catering companies obtained passing rating based on the result of the monitoring checklist. The study strongly recommends tighter implementation of the company's food safety policies among catering companies. Moreover, food establishments are challenged to address the food safety concerns in their facilities such as proper design and material finishes that promote food safety.